2016
DOI: 10.1177/1468087415623910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection timing on combustion, performance and emissions of lean-burn syngas (H2/CO) in spark-ignition direct-injection engine

Abstract: This article is aimed at exploring syngas as an alternative fuel for the modern gas engines. It presents the experimental results on the effect of start of injection on combustion, performance and emissions of a direct-injection spark-ignition engine powered by syngas of H 2 /CO composition. The engine was operated with wide open throttle at minimum advance to achieve maximum brake torque. Two different start of injections were selected to represent before and after inlet valve closing and the excess air ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Both the two injection timings have their advantages with the late injection suitable for lower engine speed and the early injection suiting the high engine operation speed. Details of the study are presented elsewhere [101]. 4 shows the effect of the air-fuel ratio on the pressure profile, heat release rate and MFB for different λ at 2100 rev/min.…”
Section: Medium Calorific Value Gasification Gas Combustion (50% H 2 mentioning
confidence: 99%
“…Both the two injection timings have their advantages with the late injection suitable for lower engine speed and the early injection suiting the high engine operation speed. Details of the study are presented elsewhere [101]. 4 shows the effect of the air-fuel ratio on the pressure profile, heat release rate and MFB for different λ at 2100 rev/min.…”
Section: Medium Calorific Value Gasification Gas Combustion (50% H 2 mentioning
confidence: 99%
“…Result of efficiency loss analysis showed that high-temperature combustion was the major contribution to efficiency reduction under high load conditions, whereas the gas exchange process and elongated burn duration were the largest contribution under low load conditions. Hagos et al 22 investigated the effect of injection timing on the combustion, performance, and emission characteristics of syngas in direct injection spark ignition engine. Even though fast combustion of syngas suggested late injection for a better combustion, performance and emission, the lower calorific value resulted in operational limitation for the direct injection system particularly at a higher speed maintaining the air–fuel ratio close to stoichiometry.…”
Section: Introductionmentioning
confidence: 99%